Effect of visible and ultraviolet light on TL study of topaz glass composites - Sardar, M.; Souza, D. N.; Caldas, L. V. E.; Tufail, M. (Scientia Plena, 2012)
Topaz, a naturally occurring aluminium fluorosilicate mineral, shows thermoluminescence (TL) after irradiation to beta and gamma rays. Topaz samples were collected from the Nyit mine in the Baltistan region in northern Pakistan and grinded to make powder. The powder of topaz was mixed with that of window glass in ratio of 2:1 of weight to form topaz-glass composite. The purpose of this experimentation was to study the TL characteristics and the effect of visible and ultraviolet (UV) light on composites after irradiation with beta source. The composite was irradiated at 0.1 –2000 Gy. The TL glow curves exhibit two peaks within 100 – 115oC (peak 1) and 141 – 163oC (peak 2). With the increase of dose, the intensity of peak 2 increased linearly without any change in its positions within the statistical uncertainty. The linear correlation coefficients for the peaks 1 and 2 were 0.98 and 0.99 respectively. The influence of visible and UV lights on the TL emission of beta irradiated composite revealed an increase in the TL intensity that may be due to photo-transference of charge. The reproducibility in TL response after five cycles of reuse of the composite was found to be same within ± 6% statistical uncertainty. It can therefore be inferred that the composite of glass with topaz from Nyit mine is a suitable material for beta dosimetry.